Sequential Treatment with Pazopanib and Everolimus in Metastatic Renal Cell Carcinoma - Rossetti, Sabrina; D'Aniello, Carmine; Iovane, Gelsomina; Scagliarini, Sarah; Laterza, Maria M.; De Vita, Fernando; Savastano, Clementina; Cartenì, Giacomo; Porricelli, Maria A.; Berretta, Massimiliano; Pisconti, Salvatore; Facchini, Gaetano; et al. (Frontiers in Pharmacology, 2017)
In metastatic renal cell carcinoma, complete response to first-line antiangiogenic agents is rare and resistance to therapy often develops. Protocols for sequential treatment with angiogenesis and mTOR inhibitors are under evaluation to improve outcomes. In this observational, real-world study, patients received a first-line therapy with pazopanib until discontinuation for disease progression or toxicity, then a second-line with everolimus. Primary endpoints were overall survival (OS) for sequence, progression free survival (PFS) for each agent, and safety. Thirty-one patients were included in the analysis: 73.3% of patients underwent nephrectomy before treatment, 25.8% had at least three comorbidities. At the beginning of therapy, the median age was 68 years, with more than 60% of patients older than 65 years. The median OS for sequence was 26.5 months (95% CI 17.4-nc); median PFS was 10.6 months (95% CI 6.3-12.1) with pazopanib and 5.3 months (95% CI 3.8-6.7) with everolimus. The median persistence in pazopanib therapy was 8.1 months (Interquartile Range IQR 5.3-12.7), with 31% of patients who required dose reduction, while persistence in everolimus was 4.4 months (IQR 3.4-6.5). Sequence was well tolerated with a different profile of adverse events for each agent. These data confirmed that pazopanib was effective, even in reduced dosing, and well tolerated and suggested that everolimus may represent an opportunity to continue a therapy when patients cannot further tolerate angiogenesis inhibitors or develop a resistance.